The New Testament speaks ; v. 1 explaining the New Testament as it was understood by its first readers - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1974)
Contents : v.1 : The four gospels.
Brethren writer. Donated by the author.
Keywords: Bible. N.T. -- introductions